Revolusi Pendidikan: Analisis Kurikulum Merdeka Sebagai Inovasi Pendidikan - Andrean Syahbana; Masduki Asbari; Vinni Anggitia; Hwang Andre (AGUSPATI RESEARCH INSTITUTA, 2024)
The educational revolution is a fundamental change in the education system which aims to improve the quality and relevance of education in facing the demands of the times. One of the educational innovations that is attracting attention is the Independent Curriculum. In this paper, an analysis of the Independent Curriculum as an educational innovation will be carried out. The research method used is a descriptive analytical study to collect information about the Merdeka Curriculum and analyze its strengths and weaknesses. The main issues that will be discussed are the concept of the Independent Curriculum, its implementation, and its impact on education in Indonesia. It is hoped that the conclusions from this analysis can provide a better understanding of the Independent Curriculum as an educational innovation.